The Model for Decreasing the Costs in Supply Chain with Importance of Suppliers (Global Journal of Human-Social Science, 2014)
The article deals with a design of model for decreasing costs in the supply chain with especially importance of alternative suppliers on the base model of authors Bahareh Amirjabbari, Nadia Bhuiyan and their cost minimization model with adjustment of safety stock. Paper shows the formulation and design of cost model with outlining a model in a particular case study to supply chain with two suppliers and with their respective independent alternative suppliers, stream of material, manufacturing in plant, safety stock and two final customers and used the conclusion of case study for further research with design appropriate model for distribution of final parts to costumers. The goal of this paper is a model and its application to reduce costs in supply chains using contracted suppliers and their probability of delivery in conjunction with alternative suppliers and their performance.
Keywords: costs; supply chain management; cost model; probability; delivery performance; equations; alternative supplier